Factores psicosociales que median la apropiación social del espacio desde la perspectiva de 33 dirigentes barriales del distrito metropolitano de Quito durante el año 2013 - Almache Freire, Sonia Lizet (2016)
The aim of this work is to know which are the psychosocial factors that mediate the social appropriation of the space according to the perspective of 33 sectoral leaders from the metropolitan district of Quito during 2013. The population are scarce economical resources people that due to the big cities development, in this case Quito, emigrate from countryside or small cities with the final purpose of being include in the economic progress, with this comes up the necessity of rely on a habitat, a space with social basic services, where people can have safety and the appropriate development of the families, improving their life quality. The theoretical framework is based on community and environment psychology postulates, the working methodology is qualitative order, our research is descriptive, as data collection instruments we did semi-structured interviews and for the analysis we focus on the proposal of the founded theory allowing us to recognize the psychosocial factors in the social appropriation of the space. We can see a psychosocial factor model that allows the development of the collective action same that finishes in the popular fight to improve the life quality.